2021
DOI: 10.5935/1984-0063.20200107
|View full text |Cite
|
Sign up to set email alerts
|

Child perception and parent’s perception about child sleep quality

Abstract: Introduction:Sleep is a physiological necessity that interferes with the activity during the day. This study aimed to analyze child perception about sleep quality and compare it with parent's perception about the quality of their children's sleep, and to investigate the sleep quality of Portuguese schoolchildren. Analyze the differences between the sexes and the type of school attended. Material and Methods: Cross-sectional study, quantitative methodology. The results of two questionnaires, the Pittsburgh slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
1
1
2
Order By: Relevance
“…Compared with previous studies of Chongqing City of China in 2011 (PSQI score: 5.51 ± 2.57), Hunan primary school students have better sleep quality than them [ 29 ]. In 2021, a Portuguese study showed that the PSQI reported by children aged 6–10 was 4.05 ± 2.803, slightly lower than the score of this study [ 30 ].…”
Section: Discussioncontrasting
confidence: 62%
“…Compared with previous studies of Chongqing City of China in 2011 (PSQI score: 5.51 ± 2.57), Hunan primary school students have better sleep quality than them [ 29 ]. In 2021, a Portuguese study showed that the PSQI reported by children aged 6–10 was 4.05 ± 2.803, slightly lower than the score of this study [ 30 ].…”
Section: Discussioncontrasting
confidence: 62%
“…A faixa etária entre 18 a 85 anos, sendo 40,35% de 31 a 40 anos e 29,82% de 21 a 30 anos, no qual a prevalência de deficientes físicos foi entre 20 e 40 anos 9 . Houve uma prevalência de 55,6% de mulheres cadeirantes em relação aos homens, com 44,4%, neste houve prevalência do sexo masculino 35 (61,4%) e 22 (38,6%) do sexo feminino 10 .…”
Section: Discussionunclassified
“…Dados que em relação ao recurso se diferm, no qual os recursos da TA não atendem as necessidades de seus usuários, logo não havendo um bom nível de satisfação para com ele, assim sendo uma influência negativa para a qualidade de vida do usuário 19 . Já em relação a dimensão serviço da TA, os estudos já citados anteriormente, também apresentaram correlações significativas entre essa dimensão e a qualidade de vida dos usuários, sendo que nestes estudos a relação entre essas variáveis foram negativas [1][2][3][4][5][6][7][8][9][10][11][12][13] .…”
Section: Discussionunclassified
“…The results expressed a contradiction between children and parents perception as PSQI revealed good sleep quality and CSHQ poor sleep quality. Authors explored some hypothesis for the reason of this different perception between parents and children 5 . Although interesting, results should be further explored.…”
mentioning
confidence: 99%